Melatonin and beta-glucan alone or in combination inhibit the growth of dunning prostatic adenocarcinoma - (:unkn) unknown (My University, 2011)
In this study, the effects of melatonin or beta-glucan treatments on tumor growth, pro-oxidant, and antioxidant status in tumor tissue were investigated in Dunning 3327 MatLyLu prostatic adenocarcinoma model. Prostate cancer (PCa) was induced by single intradermal injection of 2 x 10(4) MatLyLu cells into the right hind leg of Copenhagen rats. Melatonin (10 mg/kg/daily; IP) or beta-glucan (50 mg/kg/daily; orally) treatments applied alone and together continued for 39 days. Melatonin or beta-glucan treatments alone or together inhibited tumor growth and decreased malondialdehyde (MDA) levels in tumor tissues of Dunning rats. However, there were no significant differences in tumor volumes and MDA levels among treatment groups. Melatonin and melatonin + beta-glucan treatments elevated glutathione (GSH) levels and superoxide dismutase, glutathione peroxidase, and glutathione transferase activities in tumor tissues. However, beta-glucan treatment did not influence GSH levels and antioxidant enzyme activities in tumor tissue of Dunning rats. These results indicate that melatonin and beta-glucan treatments alone or together inhibit tumor progression and oxidative stress in tumor tissues of rats with Dunning PCa.
Keywords: Animals; Male; Rats; Antioxidants; Disease Models, Animal; Melatonin; Adenocarcinoma; beta-Glucans; Blotting, Western; Glutathione; Glutathione Peroxidase; Glutathione Transferase; Lipid Peroxidation; Malondialdehyde; Oxidative Stress; Prostatic Neoplasms; Superoxide Dismutase; Tumor Cells, Cultured